Membangun Masyarakat Berwirausaha: UMKM, Fintech, dan Risikonya - Nenny A; Arko P; Saut P; Ktut Silvanita Mangani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
To support community service activity, a collaboration has been carried out with the Regional Government of the Mentawai Islands Regency and the Ugla Mentawai Simariuriu Foundation. This community service activity aims to build the community's economy in the Mentawai Islands Regency. The activity is carried out in the form of a Web Seminar (Webinar). The activity involved lecturers from various disciplines, as well as the UMKM National Secretariat, the Koperindag Office and the Mentawai Islands District Government. Activities are carried out in the form of seminars/webinar with the theme